Change in relative abundances, more so than species turnover, modulates ß-diversity and network complexity in communities of eukaryotic microorganisms from glacial to periglacial environments - Modenutti, Beatriz; Vega, Evelyn; Bastidas Navarro, Marcela; Martyniuk, Nicolás; Balseiro, Esteban (Frontiers in Ecology and Evolution, 2025)
The cryosphere is facing unprecedented changes due to global change, and one of its main consequences is on the connectivity of ice-snow and downstream habitats in the glacial and periglacial landscape. Here, we analyze the eukaryotic community composition and the ecological processes structuring eukaryotic communities in the glacial environment of Mount Tronador (North-Patagonia, Argentina). The study was carried out in Castaño Overo and Alerce glaciers, including three different compartments: glacial ice, snow, and ponds in the glacier forefield. All compartments showed low dissolved and particulate nutrient concentrations. Genomic DNA analyses revealed a high eukaryotic microorganism’s diversity, and a high proportion of shared taxa (>35%), resulting in low presence-absence ß-diversity. However, abundance-based ß-diversity is higher among compartments, underscoring that changes in abundances are significant regardless of the large number of shared ASVs. Ice and snow showed a predominance of Fungi, while Chlorophyta increased its importance in ponds. Ciliophora and Dinoflagellates were almost exclusively present in ice and ponds, respectively. The co-occurrence network analysis showed a higher number of modules and modularity in ice and snow relative to ponds. The presence of modules with algae and fungi (Pucciomycotina and Chytridiomycotina) would reflect a functional association due to the nutritional dependence of fungi on the algae. More connectors between modules were detected in ice and snow (5 and 6) relative to ponds (only 1). Most of these connectors were fungi that could also indicate their dependence on more than one species association (module). Overall, our results showed that as ice and snow melt due to global change, eukaryotes will undergo community reorganization that will affect downstream environments.